PENGELOLAAN PANTAI WISATA BAHARI JAWAI SELATAN SEBAGAI OBJEK WISATA DI KECAMANTAN JAWAI SELATAN KABUPATEN SAMBAS - Wahab Wahab (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The purpose of this study was to find out how the management of tourist attractions, especially on pantai Bahari in Jawai Laut Village, Kec. Jawai Selatan. Where this tourist spot is managed directly by the local community which is a source of income for local residents so that it can improve the economy of the local community for the better. This research was conducted by interview, then the data that had been collected was analyzed using descriptive analysis. The results of this study indicate that the management of tourist attractions is carried out in mutual cooperation with the surrounding community but remains structured in terms of management management and organizational structure.